Smoking is worth the risk: Understanding adolescents' rationalisation of their smoking behaviour - Tohid H.; Omar K.; Muhammad N.A.; Jaffar A.; Md Monoto E.M.; Mohd Ishak N. (Universiti Putra Malaysia, 2024)
Indexed by WOS/ Scopus